Comparatif Analysis of Production Factor Efficiency of Molded and Crystal Coconut Sugar Businesses in Banyumas Regency - Nur Indah Cahyaningtyas; Liska Simamora; Muhammad Luthfie Fadhilah; Levana Masitajasmin Putri (Kirana Publisher (KNPub), 2026)
Coconut sugar agroindustry is one of the important rural economic activities that contributes to household income and local economic development. Differences in production systems between molded coconut sugar and crystal coconut sugar businesses may influence the efficiency of production factor utilization, particularly in the use of sap as the main raw material. This study aimed to identify differences in the efficiency of production factor use between molded coconut sugar and crystal coconut sugar businesses. The research employed a quantitative approach using comparative analysis of production factor use efficiency in both types of businesses. Primary data were collected through interviews and observations of coconut sugar producers. The results showed that the efficiency value of sap utilization in molded coconut sugar businesses was 1.02, while the efficiency value in crystal coconut sugar businesses was 1.03. These findings indicate that both businesses were relatively efficient in utilizing sap as a production factor because the efficiency values were greater than one. However, the efficiency levels were not yet optimal due to unpredictable rainy and dry seasons, which affected the quantity and quality of sap production. Fluctuating weather conditions caused inconsistencies in sap yield and influenced the effectiveness of production activities.